Reflexões sobre o Modelo de Desenvolvimento Rural e Cooperação no Corredor de Nacala - Natacha Bruna (Cadernos de Estudos Africanos)
The main objective of this paper is to critically address the existing rural development model in Mozambique focusing on the Nacala Corridor by analyzing the dynamics, external and internal actors, rural development strategies and policies in the region. Some trends and implications of the region’s development model were identified: land grabbing and appropriation of natural resources, resulting in involuntary migrations and deterioration of the quality of life and intensification of poverty levels of the poorer classes, presence of strategic alliances that disproportionately allow accumulation of wealth among different social classes, the emergence of investment and cooperation of actors from the Global South with strategic alliances with actors from the Global North and a resulting intensification of Mozambique’s economic dependence.